2016
DOI: 10.3390/ma9070554
|View full text |Cite
|
Sign up to set email alerts
|

Tunability of Size and Magnetic Moment of Iron Oxide Nanoparticles Synthesized by Forced Hydrolysis

Abstract: Abstract:To utilize iron oxide nanoparticles in biomedical applications, a sufficient magnetic moment is crucial. Since this magnetic moment is directly proportional to the size of the superparamagnetic nanoparticles, synthesis methods of superparamagnetic iron oxide nanoparticles with tunable size are desirable. However, most existing protocols are plagued by several drawbacks. Presented here is a one-pot synthesis method resulting in monodisperse superparamagnetic iron oxide nanoparticles with a controllable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…The M-H loops of the both sets of particles are shown in Figure 6 . Consistent with previously published data, the larger particles exhibited higher saturation magnetization, likely due to better developed crystallinity [ 37 , 38 , 39 ]. Both 100 nm and 225 nm particles saturated at approximately 1000 Oe applied field.…”
Section: Resultssupporting
confidence: 91%
“…The M-H loops of the both sets of particles are shown in Figure 6 . Consistent with previously published data, the larger particles exhibited higher saturation magnetization, likely due to better developed crystallinity [ 37 , 38 , 39 ]. Both 100 nm and 225 nm particles saturated at approximately 1000 Oe applied field.…”
Section: Resultssupporting
confidence: 91%
“…This corresponds to a 5-fold and 8-fold increase in magnetization, when comparing based on nanoparticle mass and iron mass, respectively. These values also exceed the magnetic saturation of 66 emu/g reported for 20 nm SPIONs [32]. Interestingly, previous studies showing modification of magnetite nanoparticles usually imply a reduction of their magnetization, compared with pure SPIONs [13,[33][34][35][36].…”
Section: Magnetic and Optical Propertiesmentioning
confidence: 48%
“…Studies have shown that particle size can impact the effectiveness of Prussian blue in treatment of heavy metal poisoning [55,56]. Moreover, it has been shown that the size and shape of single-domain particles can affect their magnetic properties, which may influence their behavior in magnetic manipulation and heating applications [32,[57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there has been a continual desire to develop more effective SPIONs. The magnetic moment of a particle is typically proportional to its size (Rosensweig, 2002;Sutens et al, 2016); therefore, numerous strategies have been developed to increase SPION size. For example, seed growth is a well-studied method of gradually growing monodisperse SPIONs up to 20 nm in diameter (S. Sun et al, 2004); unfortunately, although this process produces very monodisperse particles, the gradual size increase in multiple steps lengthens synthesis time.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%